High nuclear MSK1 is associated with longer survival in breast cancer patients - Pu, Xuan; Storr, Sarah J.; Ahmad, Narmeen; Rakha, Emad; Green, Andrew R.; Ellis, Ian O.; Martin, Stewart G. (Springer, 2018)
Purpose: Mitogen- and stress- activated kinases (MSKs) are important substrates of the mitogen-activated protein kinase (MAPK)-activated protein kinase family. MSK1 and MSK2 are both nuclear serine/threonine protein kinases, with MSK1 being suggested to potentially play a role in breast cancer cell proliferation, cell cycle progression, cell migration, invasion and tumour growth. The aim of the current study was to assess MSK1 protein expression in breast cancer tumour specimens, evaluating its prognostic significance.